Necessity of Routine Chest Radiograph Following Chest Tube Removal in Pediatric Patients After Cardiovascular Surgery. Issue 1 (17th January 2023) - Slak, Peter; Winant, Abbey J.; Lee, Edward Y.; Plut, Domen
Abstract : Purpose: Chest tube placement and subsequent removal is a routine step in patient management after cardiovascular surgery. The purpose of this retrospective study is to determine the necessity of routine chest radiography following chest tube removal in order to detect potential complications in pediatric patients after cardiovascular surgery. Materials and Methods: We retrospectively reviewed the hospital records of all consecutive children up to 5 years of age who had cardiovascular surgery at our hospital between January 2015 and December 2020. Two radiologists independently evaluated routine chest radiographs performed 4 hours following chest tube removal for the presence of potential complications. In all post chest tube removal chest radiographs that demonstrated a complication, the patient's medical record was investigated in order to determine if there was an associated clinical or laboratory test abnormality, and if the radiographically detected complication led to a change in patient management. Inter-rater agreement between the 2 reviewers was evaluated with κ statistics. Results: We identified 147 children (73 [49.7%] male and 74 [50.3%] female; mean age=13.8 mo old; range 0 to 60 mo) who met the inclusion criteria. Complications were detected on routine chest radiograph after chest tube removal in 10 patients (6.8%) including pneumothorax (n=5, 3.4%), pleural effusion (n=3, 2%), pneumomediastinum (n=1, 0.7%), and pneumopericardium (n=1, 0.7%). No clinical or laboratory abnormalities were present in all children affected with radiographically detected complications on routine chest radiograph 4 hours after chest tube removal, and there was no need for intervention in any affected patients. There was high inter-rater κ agreement between the 2 independent reviewers for detecting complications on chest radiographs after chest tube removal (κ=0.94). Conclusion: Our study shows that routine chest radiograph performed shortly after chest tube removal may not be necessary for the safe management of asymptomatic children after cardiovascular surgery because complications are rare and do not require intervention. In addition, obviating performance of this routine chest radiograph following chest tube removal will lead to a substantial decrease in exposure to unnecessary ionizing radiation in children who undergo frequent radiographs and lower medical costs.